Efektifitas Pemberian Olesan Jahe Merah Terhadap Penurunan Keluhan Nyeri Sendi pada Lansia - Rahayu Novi Widyastuti (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2013)
Background: The process of being old is the process that naturally occurs in the elderly as a result of a decrease in all organs. This makes a lot of elderly complaints that can disturb their comfort and decrease their standard in fullfilling their needs in their life. Thus, the elderly may suffer from painful rheumatic surrounding the joint. The cause of illness or pain can be due to rheumatism, uric acid, or osteoatritis. If the complaints are not treated well, they may result in a decrease in activity, social isolation, sleep disturbances and fall. This research aims to determine the effectiveness of ginger rub tothe decrease of painful joints complaints in the elderly in PSTW Luhur Budhi. Method of research: This is an experiment research using the method of experiment and the design research of One Group Pretest-Postest which is conducted on the elderly who stay in the PSTW Budhi Luhur Yogyakarta, on April 3, 2009 until May 3, 2009. The elderly who become the sample in this research are the elderly who have painful joints complaints. There are 10 samples in this research taken as the respondents. Thedata collection is obtained using interviews and the questionnaires uses instrument intensity of joint pain that is called a numeric scale. Research results: The finding of this research shows that there is a decrease in the number of painful joints complaints between pretes and postes namely pretes of low pain 30%, low pain postes becomes 80%, medium pain pretes are 70% to medium postes 10%, and there is no category of pain postes as 10%. This result is not much different with the results of the test using Wilcoxon statistics. Based on the analysis results, it is obtained p value = 0.014 (p <0.005), so that Ha is accepted and Ho is rejected. This means that the rub of red ginger is effective against the decrease in joint pain complaints in the elderly in PSTW Budhi Luhur Yogyakarta. The elderly who have painful joints complaints can take this red ginger as a medicine to reduce or eliminate joint pain complaints rather than the use of chemical medicines that commonly have side effect.